Effects of bioactive constituents extracted from Musa x paradisiaca flower on milk production in Vivo - Mahmood, Azizah; Omar, Muhammad Nor; Ngah, Nurziana (Lippincott Williams & Wilkins, 2011)
Many plants are reputed to possess galactagogue activity that can be consumed to increase milk production for the need of the young. These plants should have contained possible substances that interact and affect lactation in mothers. In this research, two compounds (C1 and C2) were extracted from Musa x paradisiaca flower to determine its effect on milk production. 30 lactating rats of Spraque Dowley strain were daily administered with samples started from Day 5 through Day 15 of lactation using feeding tubes. The performance of milk production were measured a day after, started from Day 6 through Day 16 by means of weight-suckle-weight method after a 6 hr separation of litters from their dams. Results of the studied compounds were statistically analyzed and compared to the aqueous crude extract, metachlopromide and control groups using SPSS by means of ANOVA at 0.01 level of significant. Milk production of C1 and aqueous crude extract groups were significantly higher compared to C2, metachlopromide, and control groups. C1 was identified to increase milk production by 28.03%, while aqueous crude extract by 24.87%. The mean of milk yield within the given suckling period in gram of crude extract, C1, metachlopromide, C2, and control group were 4.86, 4.65, 3.76, 3.68 and 3.63, respectively. The peak lactation time of the experimental groups was either at Day 13 or Day 14 of lactation period. It was concluded that the bioactive compound (C1) exist in the flower could be the possible compound which affected milk production. The extract from Musa x paradisiaca flower could be utilised to increase milk yield, thus its function as lactogenic food is recommended for mothers of inadequate milk production.